State of flow and its relationship with Anxiety levels in a sample of nurses working at Damascus Hospitals (Damascus University Journal of educational and Psychologyical sciences, 2021)
The research aimed at identifying the level of flow, and the level of anxiety as well as identifying the relationship between flow (and its sub- components) and anxiety, and exploring the differences among nurses in flow and anxiety according to the  gender and duration of service . The sample of this research consisted of (102) nurses :(31)males, (71) females. The instruments of the research included flow scale and anxiety scale . Results showed the following :there were average levels of flow and anxiety among the sample of the research, and the average level of anxiety predicts flow. There was a negative statistically significant correlation between flow (and its sub –components) and anxiety. There were no statistically significant differences in flow (and its sub –components) according to gender .There were statistically significant differences in flow (and in its sub-components)according to the duration of services, and these differences were in favor of  the increase of the length of service  . There were no statistically significant differences in anxiety according to gender. there were statistically significant differences in anxiety according to the duration of service, and these differences were in favor of minimum length of service. there were significant differences between high and low –flow in anxiety in favor of low flow .
Keywords: Flow; Anxiety